DISKRIMINASI ETNIS TIONGHOA DI GORONTALO MASA ORDE BARU - Latif, Fikryanto R.; Yulan, Yulan; Malae, Andris K. (Jambura History and Culture Journal, 2022)
The New Order was a gripping order for the ethnic Chinese community, how could they not get different treatment at that time when massive discrimination by the Indonesian government had a major impact in all corners of Indonesia. This discriminatory behavior was caused by several factors, including the occurrence of the "coup" in 1965, because it was suspected that China participated in the Indonesian Communist Party in the "coup" of 1965. After the "coup" in 1965, the situation in the People's Republic of China and Indonesia worsened, which influenced the New Order government's policy towards ethnic Chinese and led to discriminatory behavior. This discrimination occurred in Gorontalo, so that places of worship and schools for Chinese were closed and they were not allowed to perform their traditional ceremonies.